The The Nexus Of Management Model And Social Transformation: A Case Study Of Da'Wah Strategy At The Jogokariyan Mosque - Arsam Arsam; Nik Suhaida Nik Abdul Majid; Asep Amaludin (Universitas Islam Negeri Walisongo Semarang, 2026)
Non-Indexed Publication